Assessing the treatment effect of cranberry type A proanthocyanidins on vulvovaginal candidiasis: a randomised controlled clinical interventional study - Yueyue Chen; Dongmei Wei; Xiaoyu Niu; Yaoming Chen; Tao Cui (BMJ Publishing Group, 2024)
Objective This study aimed to evaluate the efficacy and safety of cranberry extracts: A-type proanthocyanidins (A-PACs) in the treatment and prevention of vulvovaginal candidiasis (VVC).Method An open, randomised, parallel-design study was conducted. A cohort of 300 eligible patients with VVC was recruited from the hospital. All participants were randomly divided into three groups according to a computer-generated randomisation list. Patients in group 1 were treated with standard antifungal therapy (oral single-dose fluconazole 150 mg and vaginal miconazole suppository 400 mg at bedtime for 3 days); patients in group 2 received oral A-PACs 16 mL two times per day for 6 days based on the treatment regimen of group 1; patients in group 3 were given oral A-PACs 16 mL two times per day for 6 days and vaginal miconazole suppository 400 mg at bedtime for 3 days. Patients who were clinically cured at the seventh day of follow-up in group 2 received maintenance therapy by oral A-PACs for 12 weeks.Result At the seventh day of follow-up, the vaginal mycological results of all patients in group 2 who initially tested positive for pseudohyphae exhibited negative results. The negative conversion rates of fungal spores and blastospores in group 2 were superior to those in both group 1 and group 3. The symptoms of patients in group 2 ameliorated conspicuously compared with those in group 1 (p<0.05). The clinical cure rate of VVC in both group 2 and group 3 was not inferior to group 1. Cox regression analysis showed maintenance therapy was not significantly associated with short-term recurrence (HR 0.44 (0.11, 1.67); p=0.23) but could significantly diminish the risk of long-term recurrence (HR 0.57 (0.33, 0.99); p<0.05).Conclusion This study revealed that A-PACs in cranberry juice combined with azole antibiotics can be used as a novel therapeutic option for the treatment and prevention of long-term recurrence of VVC.Trial registration number ChiCTR2300076392.